Obesity and other risk factors: The National Survey of U.S. Long-Haul Truck Driver Health and Injury - Sieber, W. Karl; Robinson, Cynthia F.; Birdsey, Jan; Chen, Guang X.; Hitchcock, Edward M.; Lincoln, Jennifer E.; Nakata, Akinori; Sweeney, Marie H. (American journal of industrial medicine, 2014)
Background Drivers of heavy and tractor‐trailer trucks accounted for 56% of all production and nonsupervisory employees in the truck transportation industry in 2011. There are limited data for illness and injury in long‐haul truck drivers, which prompted a targeted national survey. Methods Interviewers collected data during 2010 from 1,670 long‐haul truck drivers at 32 truck stops across the 48 contiguous United States that were used to compute prevalence estimates for self‐reported health conditions and risk factors. Results Obesity (69% vs. 31%, P < 0.01) and current smoking (51% vs. 19%, P < 0.01) were twice as prevalent in long‐haul truck drivers as in the 2010 U.S. adult working population. Sixty‐one percent reported having two or more of the risk factors: hypertension, obesity, smoking, high cholesterol, no physical activity, 6 or fewer hours of sleep per 24‐hr period. Conclusion Survey findings suggest a need for targeted interventions and continued surveillance for long‐haul truck drivers. Am. J. Ind. Med. 57:615–626, 2014. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.